(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article tells about the newsreel Peoples Courage, created by the famous film director Ali Khamroev based on archival materials. This documentary film dedicated to the Great Patriotic War was presented on the 75th anniversary of the victory. The film provides audience with historical information based on well-documented facts. The perseverance and courage shown by the Uzbek people during the Great Patriotic War are captured in documentaries. In this article, we decided to examine these processes.